Approach to Upper Gastrointestinal Bleeding - When to Treat? - P Rutgeerts (Canadian Journal of Gastroenterology)
Upper gastrointestinal bleeding from peptic ulcer is a life threatening emergency. Clinical risk factors for fatal outcome have been defined, and endoscopic predictors for rebleeding have been identified. Active ulcer bleeding at endoscopy carries an 80% chance of persistent or recurrent bleeding. A non bleeding visible vessel is associated with a 50% chance of rebleeding. These endoscopic lesions should be treated endoscopically. Failure to obtain definitive hemostasis endoscopically will necessitate emergency surgical treatment.